Pengembangan Kurikulum Tahfidz Alquran; Studi Kasus Di MA Mambaul Ulum Tunjungmuli Purbalingga - Ardan By Chully; Abbas Sofwan Matlail Fajar (UIN Syarif Hidayatullah Jakarta, 2023)
A dichotomous science paradigm must be changed. The curriculum emphasizes intelligence. Curriculum development will continue to innovate and assess students' talents and learning interests. The researcher proposed the thesis